2007
DOI: 10.1088/0031-9155/52/13/022
|View full text |Cite
|
Sign up to set email alerts
|

Systematic variations in polymer gel dosimeter calibration due to container influence and deviations from water equivalence

Abstract: There are a number of gel dosimeter calibration methods in contemporary usage. The present study is a detailed Monte Carlo investigation into the accuracy of several calibration techniques. Results show that for most arrangements the dose to gel accurately reflects the dose to water, with the most accurate method involving the use of a large diameter flask of gel into which multiple small fields of varying dose are directed. The least accurate method was found to be that of a long test tube in a water phantom,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The optical density at D max ($1.6 cm) was chosen for the plot, consistent with the requirements for minimal systematic error as the dose gradient is shallow. 35 The detection limit is approximately 30 cGy and dose sensitivity is 0.02 cm À1 Gy À1 . The R 2 value is 0.9994 implying a desirable linear dose response up to the maximum measured dose of 1889 cGy.…”
Section: Iva Defgel: Calibration and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical density at D max ($1.6 cm) was chosen for the plot, consistent with the requirements for minimal systematic error as the dose gradient is shallow. 35 The detection limit is approximately 30 cGy and dose sensitivity is 0.02 cm À1 Gy À1 . The R 2 value is 0.9994 implying a desirable linear dose response up to the maximum measured dose of 1889 cGy.…”
Section: Iva Defgel: Calibration and Propertiesmentioning
confidence: 99%
“…Calibration using a large tub of gel with multiple fields has been shown to accurately represent dose to water to better than 1%. 35,36 Background scatter was assumed to be linearly correlated with beam fluence and the weighted background-subtraction scattering factor was calculated for each beam. Field edges were separated by 1 cm such that at D max the center of each field was well beyond the range of secondary electrons from the adja-cent fields, and the center of each field was contained in the 90% inner area of the PET jar.…”
Section: Iiic Radiological Properties and Calibration Of Defgelmentioning
confidence: 99%
“…Previously gel dosimeters have been restricted to either relative dose measurements or calibration via secondary methods such as separate vials or reproduction of an identical gel in a second container, both methods of which may affect the response of the gel dosimeter through variations in chemical composition, temperature history [33][34][35] or dose inaccuracies resulting from varying scatter conditions in different container geometries [36,37]. Furthermore, Taylor et al [36,37] have shown that a single large container is the most dosimetrically accurate geometry for gel dosimetry; inclusion of both detectors in the same volume ensures the most accurate results. Therefore, the inclusion of a plastic scintillator in a large container provides the opportunity for absolute dose measurements with gel dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…The PET containers (10cm diameter, 19cm height) for exposure were left in the linac room for 1 hr prior to irradiation. The first PET container (1) was irradiated to doses from 0 Gy to 14 Gy at D max by large flask geometry method (Taylor et al 2007). The second PET container (2) was irradiated with four intersecting 4 x 4cm 2 6MV field doses of 2, 5, 7, and 11Gy at the depth of maximum dose.…”
Section: Gel Calibration and Irradiationmentioning
confidence: 99%